The Immunological Mechanisms and Immune-Based Biomarkers of Drug-Induced Liver Injury - Wenhui Liu; Wenhui Liu; Wenhui Liu; Wenhui Liu; Xiangchang Zeng; Xiangchang Zeng; Xiangchang Zeng; Xiangchang Zeng; Yating Liu; Yating Liu; Yating Liu; Yating Liu; et al. (Frontiers Media S.A., 2021)
Drug-induced liver injury (DILI) has become one of the major challenges of drug safety all over the word. So far, about 1,100 commonly used drugs including the medications used regularly, herbal and/or dietary supplements, have been reported to induce liver injury. Moreover, DILI is the main cause of the interruption of new drugs development and drugs withdrawn from the pharmaceutical market. Acute DILI may evolve into chronic DILI or even worse, commonly lead to life-threatening acute liver failure in Western countries. It is generally considered to have a close relationship to genetic factors, environmental risk factors, and host immunity, through the drug itself or its metabolites, leading to a series of cellular events, such as haptenization and immune response activation. Despite many researches on DILI, the specific biomarkers about it are not applicable to clinical diagnosis, which still relies on the exclusion of other causes of liver disease in clinical practice as before. Additionally, circumstantial evidence has suggested that DILI is mediated by the immune system. Here, we review the underlying mechanisms of the immune response to DILI and provide guidance for the future development of biomarkers for the early detection, prediction, and diagnosis of DILI.